ANALISIS HASIL BELAJAR SISWA DITINJAU DARI KEDISIPLINAN BELAJAR PADA TEMA 7 SUBTEMA 1 PEMBELAJARAN 5 - Marifatul Qoniah; Muhammad Prayito; Aryo Andri Nugroho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Learning outcomes are the results obtained from the activities of learners that are evaluated and assessed by teachers. Learning discipline is a series of attitudes and behaviors exhibited by students that reflect obedience, compliance, orderliness, and discipline in the learning process. The subjects of this research are the students of class V at Tambakrejo 01 Elementary School. This research has two objectives. The first objective is to understand how learning outcomes are evaluated in terms of learning discipline in Theme 7, Subtheme 1 of Lesson 5 for fifth-grade students., while the second objective is to identify the factors that support and hinder learning discipline in the subject of Social Studies for fifth-grade students. The background of this research is the lack of student discipline in the school environment, which affects their learning outcomes. The research methodology used in this study is qualitative descriptive. Data is collected through observation, interviews, and documentation. The research findings conclude that the low learning outcomes of fifth-grade students are caused by the lack of learning discipline exhibited by students during the classroom learning process, as well as their inadequate understanding of the learning material. Factors supporting student learning discipline include students' high awareness of the importance of discipline and teacher attention to students. On the other hand, factors hindering student learning discipline include low self-awareness of students and teachers in implementing discipline.